Flame Propagation Characteristics in the Boundary Layer of the Bio-Water-Coal Fuel Particle During its Ignition; Combustion Science and Technology; Vol. XX, iss. X - Syrodoy S. V. Semen Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Malyshev D. Yu. Dmitry Yurievich; Kostoreva Zh. A. Zhanna Andreevna; Purin M. V. Mikhail Vladimirovich (2022, 2022)
Title screen